Spider Toxin Peptide-Induced NIR Gold Nanocluster Fabrication for GSH-Responsive Cancer Cell Imaging and Nuclei Translocation - Tan, Huaxin; Liu, Sisi; He, Yaolin; Cheng, Guofeng; Zhang, Yu; Wei, Xiaojie; Hu, Lidan (Frontiers in Bioengineering and Biotechnology, 2021)
Gold nanoclusters (GNCs) have become a promising nanomaterial for bioimaging because of their unique optical properties and biocompatibility. In this study, lycosin-I peptide, which possesses highly selective anticancer activity by affecting the permeability of cancer cell membrane, was firstly modified for constructing fluorescent GNCs (LGNCs) for bioimaging of tumor cells. The obtained LGNCs exhibited strong NIR fluorescence, which can be further enhanced by the peptide-induced aggregation and selectively stained three cancerous cell lines over normal cell lines with low intrinsic toxicity. After uptake by tumor cells, LGNC aggregates can be depolymerized into ultrasmall nanoclusters by high level GSH, and realize the nuclear targeting translocation. Collectively, our work suggests the potential of natural active biomolecules in designing NIR fluorescent GNCs for bioimaging.